Prevalence and risk factors for hyperuricemia and hyperuricosuria in patients with hematologic malignancies - Kunlayawutipong, Thanaput; Rattanathammethee, Thanawat; Punnachet, Teerachat; Hantrakun, Nonthakorn; Piriyakhuntorn, Pokpong; Hantrakool, Sasinee; Chai-Adisaksopha, Chatree; Rattarittamrong, Ekarat; Tantiworawit, Adisak; Norasetthada, Lalita; Louthrenoo, Worawit (Frontiers in Medicine, 2024)
Introduction Hyperuricemia is a common complication of hematologic malignancies, and hyperuricosuria in this population has shown conflicting results. This study aimed to determine the prevalence of hyperuricemia and parameters associated with serum uric acid (SUA) and urine uric acid (UUA) in patients with lymphoma and myeloproliferative neoplasms (MPN). Methods This cross-sectional study included adult patients with newly diagnosed lymphoma and MPN at the university-based hospital. Clinical characteristics were collected, and independent risk factors for hyperuricemia and hyperuricosuria were determined using multiple logistic regression. Results One hundred and sixty-five patients were included with a median age of 55 years (45.5–64) and 51.5% were males. There were 91 patients (55.2%) with lymphoma and 74 cases (44.8%) of MPN. Overall, hyperuricemia was prevalent in 43.6% with a median SUA of 6.3 mg/dl (4.6–8) and hyperuricosuria was detected in 39.4% with a median 24-h UUA of 545 mg (365.4–991). Hyperuricemia was observed in patients with lymphoma and MPN in 20.9% and 71.6%, respectively, and hyperuricosuria in 15.4% and 68.9%, respectively. In lymphoma patients, estimated glomerular filtration rate (eGFR) <90 ml/min/1.73 m2 and serum lactate dehydrogenase (LDH) ≥ 250 U/L were associated with hyperuricemia with odds ratio (OR) 3.24, 95% confidence interval (CI) 1.95–11.07, p = 0.006 and OR 2.07, 95%CI 1.62–6.97, p = 0.039), and only elevated serum LDH was related to hyperuricosuria (OR 2.37, 95%CI 1.56–14.29, p = 0.036). In MPN patients, hemoglobin levels <10 g/dl and serum LDH ≥ 640 mg/dl were independent risk factors of hyperuricosuria (OR 1.88, 95%CI 1.42–8.39, p = 0.045 and OR 6.21, 95%CI 1.49–25.74, p = 0.012). Conclusion Hyperuricemia in patients with hematologic malignancies was common, notably MPN, and parameters associated with hyperuricosuria were provided. In addition to the utilization of allopurinol in patients at high risk of tumor lysis syndrome, patients without hyperuricosuria may also be of significant interest.